Implementation of ICAP Principles through Technology Tools: Exploring the Alignment between Pedagogy and Technology - Deepika, A.; Kandakatla, Rohit; Saida, A.; Reddy, Vijaya Bhasker (Journal of Engineering Education Transformations, 2021)
Higher education institutions around the world have encountered unprecedented times in the year 2020 due to the impact of the COVID19 pandemic. All academic institutions were forced to an online mode of learning due to the sudden lockdown imposed across different countries to curb the growth of the pandemic. Faculty who were teaching courses had to radically change their pedagogy and adopt technology tools that could support virtual synchronous learning. In this paper, we explore one such effort where faculty at a private undergraduate engineering institution reimagined how they could apply and teach innovative teaching methodologies through technology tools. Faculty teaching engineering courses have to often utilize active and collaborative pedagogical techniques to help students achieve higher level cognitive outcomes and we describe how the same techniques could be implemented through online mode of teaching. All the faculty prior to the start of the semester has undergone a 3-week faculty development program on technology-enhanced learning. During the program, the faculties were encouraged to identify technology tools that can be used to implement pedagogic techniques that are aligned to the Interactive Constructive Active and Passive (ICAP) framework. We describe in the paper the process followed by the faculty to align technology tools with the various pedagogies identified for the courses. We provide a list of various pedagogies by mapping them to the ICAP framework and discuss how the technology tools were used to implement them. The discussion in this paper will provide engineering educators with much needed insights on how to implement innovative pedagogies through technology tools. The results can be used by faculty as they transition to a blended mode of learning post COVID19.